PENGARUH BIAYA LINGKUNGAN DAN PENGUNGKAPAN EMISI GAS RUMAH KACA (GRK) TERHADAP NILAI PERUSAHAAN - Damayanti Rizki, - (2019)
This research was conducted to examine the effect of costsenvironment and disclosure of greenhouse gas emissions to the value of companies in Go Public manufacturing companies for the period 2014-2017. The application of environmental costs is proxied using the CSR Activity Fee or costs of community development, disclosure of greenhouse gas (GHG) emissions is proxied using the emission indicator in GRI 4, and company value is proxied using Tobins'q. The population in this study amounted to 145 companiesmanufacturing chosen using purposive sampling method, so that the samples obtained were 32 samples. The data obtained comes from Annual Reporting and or company Sustainability Reporting published on the Indonesia Stock Exchange (IDX). The analysis technique used is multiple linear regression, with a significance level of 5%. The results of this study indicatethat environmental costs and disclosure of greenhouse gas (GHG) emissions with size company as control variable do not significantly of the value of companies.